A dança no processo formativo do educando: elementos para um entendimento da dança na/da escola - Natalia Martins Carneiro (2003)
This work is a theorical effort towards the understanding of thehistorically and socially built dance and its aim is to understand its educational dimension in the school context. The discussion of education, experience and art concepts represents the first step to understand the dance as an education element. These atr theoricaltools for the intermediate step, that seeks an analysis of the dance and its relationships with these concepts. At last, we intend to answer the fundamental question of this work: Dance, education experience in school? Discussing the mediation aspect of the dance in school is to build a view over the pedagogical aspects of the dance in school or its reality in school context; analyzing how its incentive (as experience of art) and its development (as education possibility) can be presented in school with human education goal.